Impact of Data Assets on a Company’s Market Value and Analysis of Its Path: A Case Study of TRS - Wu Shuang (SHS Web of Conferences)
Since the issuance of the “Interim Provisions on the Accounting Treatment of Enterprise Data Resources” in 2023, many companies started disclosing data assets in 2024. The impact of data assets on a company’s market value is a concern for all businesses and society. This paper takes TRS as a case and analyzes the relationship through the event study method and marginal market value increment.”. The research finds that including data assets into financial statements not only enhances the display of enterprise financial transparency but also increases the amount of assets and profits because of the investment of data resources originally recorded as expenses to assets, this improves the profitability and solvency of TRS and has a positive impact on the company’s market value. This research takes a specific company as a case study to analyze the influence of data assets on the company, and explores the practical significance of data assets, providing a reference for other companies which have not yet included data assets in their financial statements.